2012
DOI: 10.1508/cytologia.77.401
|View full text |Cite
|
Sign up to set email alerts
|

Karyological Analysis and Morphometrics of the Lesser Asiatic House Bat, <i>Scotophilus kuhlii</i> (Chiroptera, Vespertilionidae)

Abstract: Summary Karyological analysis and morphometrics of the lesser Asiatic house bat (Scotophilus kuhlii) from Thailand were studied. Blood samples were taken from 5 male and 5 female bats, lymphocytes were cultured at 37 C for 72 h in presence of colchicine, and metaphase spreads were performed on microscopic slides and air-dried. Conventional staining and GTG-banding techniques were applied to stain the chromosomes. The results showed that the diploid chromosome number of S. kuhlii was 2n=36, and the fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…NORs produce numerous gene expressions, and they are composed of more non-histone protein than other chromosome regions. These proteins induce specific dark bands (NOR positive) by the reduction of organic silver that changes silver to be dark (Gold (Supanuam et al 2012), and H. larvatus (2n=32) had two NORs positions on the long arm near the centromere of large metacentric chromosome pair 8 (Jantarat et al 2014). Furthermore, NORs are usually located close to a subcentromeric region of a chromosome arm.…”
Section: Ag-nor Banded Karyotypementioning
confidence: 99%
“…NORs produce numerous gene expressions, and they are composed of more non-histone protein than other chromosome regions. These proteins induce specific dark bands (NOR positive) by the reduction of organic silver that changes silver to be dark (Gold (Supanuam et al 2012), and H. larvatus (2n=32) had two NORs positions on the long arm near the centromere of large metacentric chromosome pair 8 (Jantarat et al 2014). Furthermore, NORs are usually located close to a subcentromeric region of a chromosome arm.…”
Section: Ag-nor Banded Karyotypementioning
confidence: 99%
“…The order Chiroptera is an interesting group with chromosome evolution ranging from considerably conservative to quite divergent (Varella-Garcia et al 1989). Chromosomal studies of bats from Thailand have reported only 36 species representing seven families (Harada et al 1982, Hood and Baker 1986, Harada et al 1985a, 1985b, Bickham et al 1986, Hood et al 1988, Wu et al 2009, Supanuam et al 2012.…”
mentioning
confidence: 99%